Exploring The Application Of Radio Frequency Sensor At Signalized Intersections For Emergency Vehicles - Nagalingam, Muvent (Universiti Sains Malaysia, 2022)
The problem of traffic congestion is a phenomenon that has a major impact on Malaysia's transportation system. This creates a slew of problems, especially when emergency situations arise at congested traffic light junctions.The main controller, control circuit, counter, timer, decoder, clock signal generator, decoder drive circuit, and digital display decoder drive circuit are all necessary components of the traffic light control system to complete the entire process of operating the traffic light. A traffic light controller system was developed to overcome these concerns. The PIC 16F877A microcontroller was used to shift the sequence back to the normal sequence before the emergency mode was activated by pressing the button on the remote. The radio signal receiver is fixed in the traffic lights and the transmitter is fixed in the remote. Because other vehicles must assemble in order for an emergency vehicle to be granted a unique route, this strategy will reduce accidents that occur regularly at traffic light crossings. As a result, this study was effective in studying and implementing wireless communication, also known as radio frequency (RF) transmission, in the emergency vehicle traffic light management system. The prototype developed in this study operates on the frequency of 315MHz and works with the cycle mode of traffic lights when an emergency vehicle passes through a junction, altering the sequence back to normal before the emergency mode is triggered. This prototype system can be enhanced in the future by controlling real-world traffic conditions, effectively upgrading current traffic signal system technology. In the future, this prototype system can be enhanced by managing the actual traffic condition, thereby enhancing the technology of the current traffic signal system.